Leveraging Knowledge Management for Business Success: The Influence of Dynamic Capabilities and Entrepreneurial Competence, Moderated by Government Policy - Komalasari, Yanti; Marnis , M.; Garnasih, Raden Lestari; Samsir, S. (Journal of Ecohumanism, 2024)
This study examines the impact of knowledge management on business performance, mediated by dynamic capabilities and entrepreneurial competence, and moderated by government policy. A survey of 156 small and medium-sized enterprises (SMEs) in the Riau Coastal Food sector was conducted, and data were analyzed using Structural Equation Modeling (SEM). The findings reveal that knowledge management positively influences business performance, with dynamic capabilities and entrepreneurial competence acting as key mediators. However, government policy does not significantly moderate this relationship. The study highlights the importance of internal organizational capabilities in enhancing SME performance, suggesting that firms must focus on dynamic capabilities and entrepreneurial competence to maximize the benefits of knowledge management.